2023
DOI: 10.1021/acs.langmuir.3c01432
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Analysis and Property Prediction of Extended Surfactants Based on the Respectively Optimized Force Field

Lintao Yu,
Simeng Gao,
Wei Ding
et al.

Abstract: Extended surfactants represent a novel class of anionic–nonionic surfactants with exceptional performance and unique application value in chemically enhanced oil recovery. Although molecular dynamics (MD) simulations can efficiently screen these surfactants, the current research is limited. Here, it is proven for the first time that existing generic force fields (GAFF and CHARMM) cannot accurately describe extended surfactants, and traditional approaches are insufficient for obtaining precise charge parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Thus, it is crucial to meticulously investigate the impacts caused by elements other than rubber, particularly phospholipids and proteins, on the behavior of NR’s SIC in order to attain a more comprehensive understanding. Impressively, existing studies have acknowledged the substantial potential of molecular dynamics (MD) simulation as a robust approach for unraveling the complexities of materials with intricate structures. MD simulation has been widely acknowledged as an effective approach for studying the crystallization behavior of polymers, as demonstrated by numerous studies. It offers a powerful tool to investigate the molecular-level mechanisms and dynamics involved in the process of polymer crystallization. However, it has been observed that in the fields of chemistry and materials science, the process of model training typically involves a limited subset of high-quality data points, which usually range from a few hundred to even fewer .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is crucial to meticulously investigate the impacts caused by elements other than rubber, particularly phospholipids and proteins, on the behavior of NR’s SIC in order to attain a more comprehensive understanding. Impressively, existing studies have acknowledged the substantial potential of molecular dynamics (MD) simulation as a robust approach for unraveling the complexities of materials with intricate structures. MD simulation has been widely acknowledged as an effective approach for studying the crystallization behavior of polymers, as demonstrated by numerous studies. It offers a powerful tool to investigate the molecular-level mechanisms and dynamics involved in the process of polymer crystallization. However, it has been observed that in the fields of chemistry and materials science, the process of model training typically involves a limited subset of high-quality data points, which usually range from a few hundred to even fewer .…”
Section: Introductionmentioning
confidence: 99%